Analisis Strategi dan Tindak Tutur Direktif Masyarakat di Pesisir Pantai dalam Komunikasi - Minto, deriwan (UNIB Press, 2023)
There is an assumption that coastal communities tend to speak loudly, loudly and without further ado. Communication can fail to understand if not addressed properly. The aim of the research was to specifically describe the strategies and speech acts to direct the people on the coast in communication. This type of qualitative research, descriptive analysis approach. Observation data collection techniques, recording and recording. Validity is semantic validation. The analysis was carried out reducing, presenting and drawing conclusions. Based on the research results, 59.86% or more than half communicated more to ask questions. Communication by